PERISTALTIC PUMP AND DETECTION SYSTEM CONTROLLED BY AN ARDUINO OPEN SOURCE HARDWARE DEVELOPED AND DESIGNED FOR APPLICATION IN A FLOW ANALYSIS SYSTEM - Soares, Fernanda S. C.; Vieira, Alan L. [UNESP]; Soares, Marcio S.; Sant'Anna, Marcus; Nascentes, Rejane; Bossu, Carla M. (Soc Brasileira Quimica, 2018)
This work describes the development of a peristaltic pump and a photometric detector, using Arduino and alternative and low-cost materials for flow analysis system. The analytical calibration curve of the acid-red-283 using the proposed system presents 0.9984 and 3.9% as the coefficients of determination and variation, and 1.1 and 3.8 mg L-1 as limits of detection and quantification, respectively. Three prepared samples of the acid-red-283 (25, 30 and 35 mg L-1) showed recovery between 99 to 104%. For construction of the peristaltic pump and the photometer using Light Emitting Diodes (LED), light-dependent resistor (LDR) were spent less than 10% of the cost was spent on a commercial system employing a peristaltic pump and a spectrophotometer. Furthermore, the peristaltic pump and the photometer developed in this work allow the implementation of practical disciplines, such as molecular absorption spectrophotometry and flow analysis system in undergraduate courses, making these instruments more accessible, especially for the chemistry students.
Keywords: flow analysis; Arduino; peristaltic pump